Advantages and Drawbacks of Plant-Based Beverages as Alternatives to Animal Milk: A Multidimensional Review - Abbou, Amina; Kadri, Nabil; Servent, Adrien; Mouhoubi, Khokha; Medouni-Haroune, Lamia; Bouiche, Cilia; Negrichi, Samira; Meghlaoui, Zoubeida; Amrane-Abider, Meriem; Bechir, Sabiha; Taouzinet, Lamia; Bougherra, Hind; et al. (The North African Journal of Food and Nutrition Research, 2025)
Background: Plant-based beverages have gained increasing prominence as alternatives to animal milk, particularly for individuals with lactose intolerance, milk protein allergies, or those adhering to vegetarian and vegan diets. The widespread adoption of these products requires a comprehensive evaluation of their multiple properties, as they possess a range of nutritional, technological, economic, and environmental benefits and drawbacks. Aims: This narrative review provides a multidimensional synthesis of the advantages and limitations associated with plant-based beverages as viable alternatives to animal milk. Methods: A systematic literature search was conducted across the Google Scholar, Scopus, ScienceDirect and PubMed databases for articles published between 2010 and 2024. A set of defined keywords yielded 183 articles, from which 68 were selected for inclusion based on their methodological rigor and thematic relevance. Results: The findings indicate that plant-based beverages are naturally free of lactose and cholesterol and often contain beneficial dietary fiber and bioactive compounds. They are also appreciated for their sensory diversity and adaptability to specific dietary preferences. However, they are generally lower in protein and essential micronutrients compared to animal milk. Furthermore, their composition exhibits significant variability, which is influenced by the raw materials (e.g., cereals, legumes, dried fruit, etc.) and the technological processing methods employed. Environmentally, these beverages generally exhibit a lower carbon footprint, yet their retail cost remains a key disadvantage for consumers. Conclusions: In conclusion, this review highlights the critical need for further research focused on enhancing the formulation of plant-based beverages to more effectively meet consumers expectations regarding nutritional value, sensory quality, and affordability. Keywords: Plant-based beverages; Animal milk; Advantages; Limitations; Manufacturing process; Nutritional properties.